(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The aim of this research is to identify the role of dimensions of talent management practices as an independent variable to enhance of the organization prestige as a dependent variable. In light of the identification of the problem, the importance of the subject in the active contribution to develop and formulate new strategies to ensure that the talent management practices are directed in a manner that leads to the effective contribution to achieve the distinctive position of the researched company. Therefore, two main hypotheses emerged from which eight subhypotheses emerge for linkage and impact. The research targeted the telecommunications sector (Zain Iraq Telecom) as a research community. The researcher adopted the descriptive analytical approach, and the data were collected through the questionnaire, personal interviews, as well as personal observations in the field of application of the research. Statistical software (SPSS_V.24) was used to analyze the data, and a number of statistical methods were used including arithmetic mean, coefficient of variation, standard deviation, to analyze and describe the data, and to use correlation coefficient (Pearson) to test correlation hypotheses and simple linear regression coefficient. In conclusion, a number of conclusions were reached, the most important of which is that talent management practices are directly related to the organization prestige. They also positively affect the organization prestige. The dimension of talent development was the most related to the organization prestige. Talent Management Performance is the most influential in the organization prestige, The research recommended the need to pay attention to the application of talent management practices because of its impact in strengthening the organization Prestige.